(untitled) (Journal of Economic Research & Business Administration, 2016)
The problems that characterize the fiscal policy of Kazakhstan as insuf-ficiently effective, identified the main problems in the functioning of the tax system of Kazakhstan. Analyzes the state and dynamics of budget rev-enues and tax revenues of the country for the purposes of the conceptual foundations of financial relations in the fiscal policy of the country. The data of the Accounts Committee for Control over Execution of the Republi-can budget. The basic priorities and objectives of tax policy at the present stage. In order to solve these problems a number of recommendations aimed at improving tax administration and fiscal policy. In recent years, research in Kazakhstan on improvement of forms and methods of manage-ment of tax processes in the conditions of innovative modernization of the economy are particularly important. There was a need for the state tax management in a particular area of scientific knowledge in the framework of the formation of an efficient system of tax administration.